Assessment of Myoelectric Manifestations of Muscle Fatigue During Repetitive Isometric Voluntary Contraction in Boys Aged 12-14 - Abir Samanta; Sabyasachi Mukherjee (OVS LLC, 2021)
Aim: To study the peculiarity of electromyography signal characteristics alternation using different sEMG parameters during repetitive voluntary isometric fatiguing contraction in adolescent boys.  Materials and methods. 12 subjects with height 148.75 ± 10 cm; Mass 38.9 ± 7.9 kg; age - 12 to 14 years were recruited. The sEMG signal alteration of external oblique, rectus abdominis, erector spinae muscles during a fatiguing plank were analyzed. A separate one-way repeated measures ANOVA was used to test the statistical significance of task time and electromyography parameters of the global core muscle in the pre-, during- and post-fatigue plank test. One-way Friedman ANOVA was applied for Shapiro-Wilk p < 0.05. The Pearson product-moment correlation coefficient with bivariate linear regressions analysis was performed between the pre-pre fatigue and post-post fatigue amplitude mean and standard deviation values. The Spearman correlation coefficient between amplitude and endurance time both in the pre- and post-fatigue state was conducted.  Results. The mean value of rectified amplitude increased (p < 0.05) for all muscles, the standard deviation of amplitude and total spectral power increased significantly (p < 0.05) for all muscles except the erector spinae muscle (p > 0.05). The power at normalized low frequency significantly changed (p = 0.05) in the erector spinae muscle. A significant change in normalized low frequency for agonist/synergist (p = 0.02) and agonist/antagonist muscles (p = 0.05) was observed. The average amplitude value had a significant positive and linear relationship with the amplitude variability both in the pre- to post-fatigue state, except the erector spinae muscle. The time to task failure was not correlated (p > 0.05) with the sEMG amplitude.  Conclusions. Increased sEMG amplitude resulted mainly from rapid additional motor unit recruitment and rate coding during muscle fatigue. The reduction of conduction velocity might affect the spectral power with a spectral shift towards low-frequency. Increased variability, agonist/antagonist co-activity during fatiguing contraction might extend the holding time. The postural fatiguing task/plank increases multiarticular joint function by involving several joints and muscles, increases variability in the contribution of synergist muscles. This factor provides an intuitive explanation about the absence of a relationship between endurance time and sEMG amplitude changes.